The Challenges of Originalism as a Theory of Constitutional Interpretation Today - Borusevičiūtė, Miranda (Teisė, 2022)
This paper analyzes originalism, which is considered to be the opposing constitutional theory to “living” constitutionalism, and presents and evaluates the main arguments of originalism and its approach on how the constitution should be interpreted, including the shortcomings of this constitutional theory. In the author’s opinion, it is important to start developing constitutional theories that would be considered more suitable in the context of the European tradition of statutory law. The paper does not search for possibilities of using originalism to interpret the Constitution of the Republic of Lithuania, which is considered to be a fundamental error.
Keywords: constitution; theories of constitutional interpretation; originalism; “living” constitutionalism